Experimental Evaluation of the Generalized Signal Droop Model With SNR Measurements Including Transponder Implementation Penalty - Viacheslav Ivanov; John Downie; Xiaojun Liang; Jason Hurley; Petr Sterlingov; Nikolay Kaliteevskiy (IEEE Photonics Journal)
We experimentally assess the accuracy of a constant output power generalized droop (COP-GD) model combined with transponder implementation penalty to predict transmission performance for single-core long-haul optical transmission systems operating at low channel launch powers and high baud rates. The droop model includes Guided Acoustic Waveguide Brillouin Scattering (GAWBS) and nonlinear interference (NLI) effects along with amplifier noise for signal-to-noise ratio (SNR) calculation in the context of long-haul systems with constant output power amplifiers. We show how the model accuracy is decreased if one of the modeling components is removed, namely, either the droop effect, GAWBS or the transponder implementation penalty. We show that inclusion of implementation penalty and GD is important for accurate performance evaluation, moreover, the transponder implementation penalty has impact both at low and high SNR ends. We compare the model including both effects to experimental transmission data over a wide link SNR range for the first time and demonstrate excellent agreement between modeling predictions and experimental results.